PENINGKATAN MOTIVASI BELAJAR SISWA SMA MELALUI E-MODUL EKONOMI INTERAKTIF DENGAN ARTICULATE STORYLINE 3 - Annisa Yulistya; Suarman Suarman; Gimin Gimin (STKIP Singkawang, 2025)
This study aims to develop an economics e-module using Articulate Storyline 3 to enhance students’ learning motivation through the ADDIE development model. The research is categorized as developmental research with a descriptive method, involving students from classes X.9 and X.10 as subjects. Instruments used in the study include questionnaires and interviews, while data were analyzed using validity tests, dependent t-tests, and descriptive analysis. The results indicate that the development process was successfully carried out. Validation tests showed excellent results: 96.35% for media, 95% for material, and 96.88% for the overall module, suggesting that the module is highly appropriate for use in teaching. In terms of student motivation, trial testing produced significant outcomes. The Sig. (2-tailed) value was 0.000 (overall) and 0.001 for class X.10, both below 0.05, confirming the module's effectiveness in enhancing motivation. Teacher observations over five sessions also showed a considerable increase in student motivation, with class X.9 reaching 85.53% and class X.10 reaching 86.87%, both rated as very high. Student responses were equally positive, with practicality scores of 94.82% (X.9) and 93.63% (X.10). Furthermore, observations of e-module use indicated strong effectiveness and practicality, with scores of 91.54% (X.9) and 91.94% (X.10). In conclusion, the economics e-module developed with Articulate Storyline 3 is both effective and practical for improving students' learning motivation.